Multi-slice CT findings in COVID-19 pneumonia: A cross-sectional multicenter study - Metin, Melike Ruşen; Bekir Külah, Melahat; Atabey, Faruk; Aydın, Hasan (E-Century Publishing Corporation, 2021)
In this cross-sectional study of 278 patients, patients diagnosed with COVID-19 per their clinical features, laboratory, and thorax computed tomography (CT) findings were evaluated in terms of the most common characteristic findings. The lesions were classified according to the disease stage. The most common findings for each phase were investigated. The typical CT results included ground glass opacity (GGO), unilateral involvement, and single lesions in the early stages, as well as bilateral involvement, and multiple lesions in the progressive and peak phases. Additionally, vascular dilatation was the most common finding after GGO. Basal segment dominance and peripheral-intraparenchymal-basal segment involvement were mostly seen in the peak-phase patients. Thus, we think that this finding is an essential key to determining that the disease is in the advanced stages. The crazy-paving pattern was also a typical finding in the early-stage patients. Cavitary lesions, pulmonary nodules, and mediastinal lymph nodes were not observed in the lungs.
Keywords: Clinical Practice Guidelines; Pneumonia; Real-Time PCR; SARS Coronavirus